2010
DOI: 10.1074/jbc.m110.104661
|View full text |Cite
|
Sign up to set email alerts
|

Structured Post-IQ Domain Governs Selectivity of Myosin X for Fascin-Actin Bundles

Abstract: Without guidance cues, cytoskeletal motors would traffic components to the wrong destination with disastrous consequences for the cell. Recently, we identified a motor protein, myosin X, that identifies bundled actin filaments for transport. These bundles direct myosin X to a unique destination, the tips of cellular filopodia. Because the structural and kinetic features that drive bundle selection are unknown, we employed a domain-swapping approach with the nonselective myosin V to identify the selectivity mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
0
37
1
Order By: Relevance
“…Several recent papers by Rock and colleagues have suggested that Myo10 displays strong selectivity for bundled actin (17,18). This finding contradicts the findings of a recent study by Sun et al (16).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Several recent papers by Rock and colleagues have suggested that Myo10 displays strong selectivity for bundled actin (17,18). This finding contradicts the findings of a recent study by Sun et al (16).…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, we believe that the bundled actin selectivity of the Myo10 chimera shown in the Rock et al studies is likely due to the conformational change of the anti-CC dimer induced by the GCN4 fusion. Nonetheless, the detailed single-molecule stepping assays performed in the Rock et al studies have provided additional evidence, albeit from a different angle, supporting the critical role that the anti-CC plays in Myo10's processive movement along actin filaments (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each ATP-driven step taken by such truncated chimeras of myosin-10 has been reported to be in the range of 18-34 nm long (16)(17)(18)(19). Furthermore, live cell fluorescence imaging studies (20, 21) using a full-length GFP-tagged myosin-10 construct showed that single molecules move in a highly directed manner within the filopodia.…”
mentioning
confidence: 99%